Epidemiological profile among residents of the Sapê do Norte Quilombola Community, Espirito Santo, Brazil - Dias de Castro Luz, Ana Alice; Bubach, Susana; Silva Saccone, Laís; Santana Franco, Maila (Guará Journal, 2024)
Quilombola communities are marked by social inequalities and difficulties in accessing health services, which directly impact the health-disease process. Thus, the objective was to describe the epidemiological characteristics related to sociodemographic aspects, illness, lifestyle, anthropometric measurements, and blood pressure among residents of Quilombola communi-ties in Sapê do Norte, Espírito Santo. Data collection was car-ried out by socioeconomic and health situation information, physical assessment of blood pressure, waist circumference, weight and height. Ninety residents of Quilombola communities were interviewed, most of whom were women, self-declared black, aged over fift y and with low education. The results related to anthropometric measurements revealed that most of the Quilombolas evaluated were overweight or obese, increased waist circumference, high prevalence of alcoholism. More than half claimed to be hypertensive and 70% of participants had altered blood pressure levels (≥130/≥81 mmHg). These data demonstrate the vulnerability and need for intervention in these communities to prevent health problems.